STATISTICAL ANALYSIS OF LARGE-SCALE STRUCTURE OF UNIVERSE - Tugay, A. V. (Одеські астрономічні публікації, 2017)
While galaxy cluster catalogs were compiled many decades ago, other structural elements of cosmic web are detected at deﬁnite level only in the newest works. For example, extragalactic ﬁlaments were described by velocity ﬁeld and SDSS galaxy distribution during the last years. Large-scale structure of the Universe could be also mapped in the future using ATHENA observations in X-rays and SKA in radio band. Until detailed observations are not available for the most volume of Universe, some integral statistical parameters can be used for its description. Such methods as galaxy correlation function, power spectrum, statistical moments and peak statistics are commonly used with this aim. The parameters of powerspectrum and other statistics are important for constraining the models of dark matter, dark energy, inﬂation and brane cosmology. In the present work we describe the growth of large-scale density ﬂuctuations in one- and three-dimensional case with Fourier harmonics of hydrodynamical parameters. In result we get power-law relation for the matter power spectrum